2015
DOI: 10.1123/ijspp.2014-0539
|View full text |Cite
|
Sign up to set email alerts
|

Peak Match Speed and Maximal Sprinting Speed in Young Soccer Players: Effect of Age and Playing Position

Abstract: This study assessed the relationship between peak match speed (PMS) and maximal sprinting speed (MSS) in regard to age and playing positions. MSS and absolute PMS (PMSAbs) were collected from 180 male youth soccer players (U13-U17, 15.0 ± 1.2 y, 161.5 ± 9.2 cm, and 48.3 ± 8.7 kg). The fastest 10-m split over a 40-m sprint was used to determine MSS. PMSAbs was recorded using a global positioning system and was also expressed as a percentage of MSS (PMSRel). Sprint data were compared between age groups and betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 16 publications
10
91
2
5
Order By: Relevance
“…The appropriate statistical test to validate the concept of generality has been suggested to be a correlation coefficient of r = 0.71 or greater [27], as this degree of association would suggest a minimum of 50% common variance (R 2 ; coefficient of determination) [11]. For further analysis, players were divided into 2 groups, fastest and slowest, based on a moderate standardized difference (ES) (i.e., 0.2 × between-groups SD) from the group average as in previous studies [28,29]. The standardized difference or effect size (ES, 90% confidence limit (90% CL)) between the fastest and slowest players in the loss of speed due to executing a COD was calculated.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The appropriate statistical test to validate the concept of generality has been suggested to be a correlation coefficient of r = 0.71 or greater [27], as this degree of association would suggest a minimum of 50% common variance (R 2 ; coefficient of determination) [11]. For further analysis, players were divided into 2 groups, fastest and slowest, based on a moderate standardized difference (ES) (i.e., 0.2 × between-groups SD) from the group average as in previous studies [28,29]. The standardized difference or effect size (ES, 90% confidence limit (90% CL)) between the fastest and slowest players in the loss of speed due to executing a COD was calculated.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For instance, match analysis using global positioning systems has shown that peak match speed is about 87% of maximal sprinting speed obtained in a sprint test, and differs by playing position (about 94% for strikers and 85% for central midfielders) 3. Although the data are from youth players, they support the hypothesis that highly trained players use only a proportion of their physical potential due to contextual factors (ie, tactics, opponents, weather, their expectations, etc).…”
Section: What We Knowmentioning
confidence: 82%
“…With regard to the first point, tactics may prevent football players from exploring their full physical potential and hence from overloading their body during matches 3. For instance, match analysis using global positioning systems has shown that peak match speed is about 87% of maximal sprinting speed obtained in a sprint test, and differs by playing position (about 94% for strikers and 85% for central midfielders) 3.…”
Section: What We Knowmentioning
confidence: 99%
“…En cualquier caso, los valores de la V max en los JR estuvieron bastante alejados de sus máximos (24.6±1.3 en sub13 y 28.6±1.1 Km·h -1 en sub14), aun siendo valores muy similares (25.4 y 27.7 Km·h -1 para sub13 y sub14, respectivamente) a los máximos encontrados en estudios anteriores (Al Haddad, Simpson, Buchheit, Di Salvo, & Méndez-Villanueva, 2015). Únicamente en la dimensión JR60 las diferencias en V max de sub14>sub13 resultaron significativas.…”
Section: Discussionunclassified